2006
DOI: 10.1136/jech.2005.036533
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of domestic violence against women in the European Union: a multilevel analysis

Abstract: Study objective: The acceptability of domestic violence against women (DVAW) plays an important part in shaping the social environment in which the victims are embedded, which in turn may contribute either to perpetuate or to reduce the levels of DVAW in our societies. This study analyses correlates of the acceptability of DVAW in the European Union (EU). Design: Three level ordinal logistic regression of 13 457 people nested within 212 localities (cities), nested within 15 countries of the EU. Sampling is mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
134
2
20

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(165 citation statements)
references
References 26 publications
9
134
2
20
Order By: Relevance
“…This finding is congruent with previous research, since individuals who consider IPVAW as such only in cases of extreme or severe violence (e.g., physical violence) are more likely to perceive other kinds of violence (e.g., emotional or verbal violence) as more "tolerable" (Gracia & Herrero, 2006a;Muehlenhard & Kimes, 1999;Taylor & Sorenson, 2005). Our results also revealed that respondents with higher levels of acceptability presented higher scores of ambivalent sexism, in particular in the hostile sexism subscale.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is congruent with previous research, since individuals who consider IPVAW as such only in cases of extreme or severe violence (e.g., physical violence) are more likely to perceive other kinds of violence (e.g., emotional or verbal violence) as more "tolerable" (Gracia & Herrero, 2006a;Muehlenhard & Kimes, 1999;Taylor & Sorenson, 2005). Our results also revealed that respondents with higher levels of acceptability presented higher scores of ambivalent sexism, in particular in the hostile sexism subscale.…”
Section: Discussionsupporting
confidence: 82%
“…Perceived severity of IPVAW has been negatively related to acceptability of IPVAW (Gracia & Herrero, 2006a;Taylor & Sorenson, 2005). Sexist attitudes have been found to be closely related to attitudes toward IPVAW (Flood & Pease, 2009;Herrero, Rodríguez, & Torres, 2017;Lila, Gracia, & García, 2013).…”
Section: The Present Studymentioning
confidence: 95%
“…In western countries IPVAW affects many women at some point in their lives [2][3][4][5][6]. Furthermore, the impact of IPVAW on women's physical and mental health, both in the short and long term, and the wider effects of IPVAW on families, communities, and society, makes it a public health priority [7][8][9]. Prevalence data in Spain, where this study was conducted, are similar to other Western countries, with estimates ranging from 4.0% to 12.4% [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In many instances, however, the social environment surrounding the victim of IPVAW is willing to act, responding in different ways when an incident of IPVAW is known. These responses to IPVAW can be classified broadly into two types (Gracia & Herrero, 2006a;Mahlstedt & Keeny, 1993;West & Wandrei, 2002): mediating responses (e.g., offering help, support and understanding, advising, helping with decision making, talking to the couple, or reproaching the offender), and reporting responses (i.e., responses that set the law enforcement in motion by reporting the incident to the authorities). Research focusing on public responses to incidents of IPVAW, however, has been sparse compared to the scholarly attention paid to other issues such as prevalence, consequences or intervention.…”
mentioning
confidence: 99%
“…For example, in the USA, the Lieberman Survey found that almost 30% of the respondents reported that they knew a woman who was currently a victim of physical abuse (Klein, Campbell, Soler, & Ghez, 1997). Also, in a survey with a representative sample of 15 countries of the European Union (European Commission, 1999;Gracia & Herrero, 2006a), 36% of male and 45% of female respondents knew a victim of IPVAW in their social circle of work, studies, family, neighborhood or friends.…”
mentioning
confidence: 99%